Experiences and perceptions of migrant populations in South Africa on COVID-19 immunization: an interpretative phenomenological analysis - Ferdinand C Mukumbang; Sibusiso Ndlovu; Babatope O Adebiyi (BMC, 2024)
Abstract Introduction Migrant populations (asylum seekers, permit holders, refugees, and undocumented migrants) living in South Africa face various individual, social, and physical circumstances that underpin their decisions, motivation, and ability to receive the COVID-19 vaccine. We conducted a qualitative study to explore the experiences and perceptions of migrant populations in South Africa on COVID-19 vaccines to inform recommendations for improved COVID-19 immunization. Methods We conducted an Interpretative Phenomenological Analysis (IPA) with 20 asylum seekers, permit holders, refugees, and undocumented migrants living in South Africa. We applied a maximum variation purposive sampling approach to capture all three categories of migrants in South Africa. Semi-structured interviews were conducted and recorded electronically with consent and permission from the study participants. The recordings were transcribed and analyzed thematically following the IPA using Atlas.ti version 9. Results Four major reflective themes emanated from the data analysis. (1) While some migrants perceived being excluded from the South African national immunization program at the level of advertisement and felt discriminated against at the immunization centers, others felt included in the program at all levels. (2) Skepticism, myths, and conspiracy theories around the origin of SARS-CoV-2 and the COVID-19 vaccine are pervasive among migrant populations in South Africa. (3) There is a continuum of COVID-19 vaccine acceptance/hesitancy ranging from being vaccinated through waiting for the chance to be vaccinated to refusal. (4) Accepting the vaccine or being hesitant follows the beliefs of the participant, knowledge of the vaccine's benefits, and lessons learned from others already vaccinated. Conclusion COVID-19 vaccine inclusiveness, awareness, and uptake should be enhanced through migrant-aware policies and actions such as community mobilization, healthcare professional training, and mass media campaigns.